2023
DOI: 10.3389/fpls.2023.1141455
|View full text |Cite
|
Sign up to set email alerts
|

Possible EU futures for CRISPR-edited plants: Little margin for optimism?

Abstract: This article addresses the scenarios that may be encountered by the first application for pre-market approval of a CRISPR-edited plant in the EU. Two alternative scenarios are considered in the short and medium term. One of these possible EU futures depends on the final drafting and approval of EU legislation on certain New Genomic Techniques, which was started in 2021 and is due to be quite advanced before the next European Parliament elections in 2024. Since the proposed legislation excludes plants with fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“… 203 , 204 However, there is a chance of new legislation being proposed to provide CRISPR-edited plants with a regulatory framework, but it is considered that the proposed legislation will not be the best possible, even if it is passed due to the constraining influence of the current GM regulatory framework. 64 And there are other views that propose that for genome editing applications, the level of robustness in the evidence currently required for the Environmental Risk Assessment of GMOs needs to be maintained. 205 …”
Section: Gm Regulation In Major Economies (Based On Gdp Ranking)mentioning
confidence: 99%
“… 203 , 204 However, there is a chance of new legislation being proposed to provide CRISPR-edited plants with a regulatory framework, but it is considered that the proposed legislation will not be the best possible, even if it is passed due to the constraining influence of the current GM regulatory framework. 64 And there are other views that propose that for genome editing applications, the level of robustness in the evidence currently required for the Environmental Risk Assessment of GMOs needs to be maintained. 205 …”
Section: Gm Regulation In Major Economies (Based On Gdp Ranking)mentioning
confidence: 99%
“…However, in recent times, there have been calls for a review of the current regulations in Europe to differentiate between genome-edited crops and transgenic GMOs, considering the precise and targeted nature of the former. This is now being debated in the EU scientific community [193][194][195][196][197].…”
Section: Gmo-free Crispr/cas9 Crops-global Thoughts and Acceptancementioning
confidence: 99%
“…Past experiences with GMOs have shown that public opposition can significantly hinder the adoption of these technologies, regardless of their potential benefits. While early surveys suggest that the public may be more accepting of gene editing compared to GMOs, especially if the modifications could be achieved via conventional breeding, there is still significant public concern and a lack of understanding about these technologies (Escajedo San-Epifanio et al, 2023).…”
Section: Public Perception and Acceptance Of Crispr-edited Cropsmentioning
confidence: 99%